Eksplorasi Perilaku Mahasiswa dalam Implementasi Pembelajaran Hybrid di IT Telkom Surabaya - Mohammad Dhani Alfian; Intan Sartika Eris Maghfiroh; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The COVID-19 pandemic that occurred has resulted in many changes in the education sector in Indonesia. Before the pandemic, Indonesia used to implement face-to-face learning methods, then changed to online learning methods, and now uses hybrid learning. Kemendikbudristek issued to organize learning activities by implementing hybrid learning policy. IT Telkom Surabaya is an educational institution that implements hybrid learning. This study uses qualitative research methods using exploration related to hybrid learning, obstacles encountered in hybrid learning, and solutions to deal with those obstacles. The exploration was carried out by conducting semi-structured interviews with twelve students from IT Telkom Surabaya. Interview results with twelve interviewees were transcribed. Transcript results were analyzed using qualitative coding method and thematic analysis. From analysis data results were found that hybrid learning at IT Telkom Surabaya was implemented quite well, but there were some obstacles experienced by students in implementing hybrid learning. These obstacles include e-learning errors, being lazy and sleepy, and having difficulty at understanding materials provided by lecturers. Students have their own ways of dealing with these problems they face. Students solve problems by asking for help from lecturers, asking friends for help, and trying to solve them themselves.